Efficacy and safety of a high power short duration ablation-index guided protocol for pulmonary vein isolation using a single catheter. (24th May 2021) - Badertscher, P; Knecht, S; Madaffari, A; Spies, F; Osswald, S; Schaer, B; Sticherling, C; Kuehne, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Catheter ablation for atrial fibrillation (AF) is the most common performed electrophysiological procedure. The cost of this procedure remains high. Purpose: To improve health care utilization, we aimed to compare the efficacy and safety of a minimalistic, streamlined single radiofrequency catheter ablation approach using high power short duration ablation-index guided protocol (HPSD) vs. a standard single catheter protocol. Methods: A circular mapping catheter free PVI with a single transseptal puncture was performed in 91 patients. A CARTO fast anatomical map was performed with the ablation catheter. Pacing maneuvers were used to confirm exit block. Procedural characteristics and success rates were compared using HPSD- vs. a standard ablation-protocol. Freedom from recurrence was defined as a 1-year absence of AF episodes > 30 s, beyond the 3-month-blanking-period. Results: Using the HPSD-protocol the median procedure, map and RF ablation time were significantly shorter in the HPSD group compared to the standard group, 84 (IQR 76-100) vs. 118 minutes (IQR 104-141), 12 (IQR 10-16) vs. 18 minutes (IQR 15-21) and 1036 (898-1184) vs. 1949 seconds (IQR 1693-2261), respectively, P < .001 for all. First-pass-PVI was achieved using the HPSD-protocol in 23 patients (74%) and the standard-protocol in 30 patients (53%), p = 0.08. Localization of conduction gaps are illustrated for the HPSD-protocol and the standard-protocol in Figure 1. The residual gap was identified using the ablation catheter only in all patients. No procedural complication were observed. At 12 months follow-up, 60 (89.6%) patients remained free from AF with no differences between groups. Conclusions: A minimalistic, CMC-free HPSD-guided PVI approach is very efficient, safe, likely cost-saving, and associated with excellent clinical outcomes at 1 year.